Knowledge and attitude regarding care of age-related hearing loss among nurses in HUSM - Rusli, Intan Yusrina (Universiti Sains Malaysia, 2024)
Age-related hearing loss, or presbycusis, is a progressive and chronic condition often characterized by bilateral hearing impairment. This complex disorder results from the cumulative effects of aging on the auditory system. With the prevalence of age-related hearing loss expected to rise, it poses a significant public health concern. However, research on age-related hearing loss remains limited, highlighting the importance of conducting comprehensive studies to improve early identification, intervention, and overall management in elderly care. This study aims to determine knowledge and attitude regarding care of age-related hearing loss among nurses in HUSM and examine the correlation between knowledge and attitude regarding care of age-related hearing loss among nurses in HUSM. A cross-sectional study design was used in this research. Participants were 220 nurses who have experience in elderly care. The data was collected using a hard copy questionnaire and Google form distributed to the respondents. Descriptive statistics were used to describe the respondent and identify the level of knowledge and attitude regarding care of age-related hearing loss among nurses in HUSM. Pearson Chi-square was used to test the correlation between variables. Study results indicated that nurses have inadequate knowledge regarding care of age-related hearing loss which is 85.9% and 14.1% have adequate knowledge. It also shows that nurses have a negative attitude regarding care of age-related hearing loss which is 67.7% and 32.3% have positive attitude. There was a weak correlation (r=0.021) and not statistically significant. The results of this study have shown an unsatisfactory level of knowledge and attitude among nurses. It is suggested to develop an educational, training, awareness program that can help the nurses accumulate experience and improve their knowledge on the elderly with hearing loss.